A practical guide to quartz crystal microbalance with dissipation monitoring of thin polymer films. Issue 7 (5th July 2021) - Easley, Alexandra D.; Ma, Ting; Eneh, Chikaodinaka I.; Yun, Junyeong; Thakur, Ratul M.; Lutkenhaus, Jodie L.
Abstract: Quartz crystal microbalance with dissipation (QCM‐D) monitoring is a powerful tool used to sensitively examine the real‐time responses of polymer films to external responses. For example, the technique is commonly used to monitor film growth, material adsorption, thin film swelling, and ion exchange. With its rapidly expanding use, this review is intended to introduce new users to the basic principles of QCM‐D, along with practical challenges and remedies specific to polymer thin films. For both new and experienced users, specific case studies are highlighted including layer‐by‐layer assembly, electrochemical QCM‐D, swelling, sensing, and biological application. Last, the review recommends future directions for research and areas of growth. Abstract :